"Beautiful powerful you" : an analysis of the subject positions offered to women readers of Destiny magazine - Jangara, Juliana (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2011)
Women's magazines are popular cultural forms which offer readers representations intended to advise women on how to work towards and achieve idealised femininities. They perform such a function within the wider socio-historical context of gender relations. In a country such as South Africa, where patriarchal gender relations have historically been structured to favour men over women and masculinity over femininity, the representation of femininity in contemporary women's magazines may serve to reinforce or challenge these existent unequal gender relations. Informed by a feminist poststructuralist understanding of the gendered positioning of subjects through discourse, this study is a textual analysis that investigates the subject positions or possible identities offered to readers of Destiny, a South African business and lifestyle women's magazine. Black women, who make up the majority of Destiny's readership, have historically been excluded from the formal economy. In light of such a background, Destiny offers black women readers, through its representations of well-known business women, possible identities to take up within the white male dominated field of business practice. The magazine also offers 'lifestyle content', which suggests to readers possible ways of being in other areas of social life. Through a method of critical discourse analysis, this study critically analyses the subject positions offered to readers of Destiny, in order to determine to what extent the magazine's representations of business women endorse or confront unequal gender relations. The findings of this study are that Destiny offers women complex subject positions which simultaneously challenge and reassert patriarchy. While offering readers positions from which to challenge race based gender discrimination "“ a legacy of the apartheid past "“ the texts analysed tend to neglect non-racially motivated gender prejudice. It is concluded that although not comprehensively challenging unequal gender relations, the magazine whittles away some tenets of patriarchy.
Keywords: Destiny Magazine; Women's periodicals; Women, Black -- South Africa -- Social conditions; Sex role -- South Africa; Femininity -- South Africa; Women -- Identity; Feminism and mass media; Femininity (Philosophy)